Front Cover: Heterogeneous Organocatalysts Based on a Triazine‐Triazole Silane Ligand (Eur. J. Inorg. Chem. 38/2018). Issue 38 (4th October 2018) - Cruz, Paula; Pérez, Yolanda; del Hierro, Isabel
Abstract : The Front Cover shows the hexagonal and worm‐like mesoporous structure of ordered organic‐inorganic hybrid materials prepared in this article. They have been synthesized by using a bridged triazine‐triazole silane precursor, which is represented on the cover by "three‐point stars". These materials have been shown to be robust and non‐air‐sensitive metal‐free organocatalysts, very active and reusable, for Knoevenagel and multicomponent condensation reactions. More information can be found in theFull Paper by P. Cruz, Y. Pérez, and I. del Hierro . For more on the story behind the cover research, see theCover Profile .